Palatal lateral approximant /ʎ/ as one of the main troublemakers in learning croatian as L2 - Dobrić, Arnalda; Bićanić, Jodan (2013)
According to the Verbotonal theory, speakers of L1 choose the closest sound from their own
phonological system instead of the correct sound when learning L2 in adult age and the errors are consistent
regarding their common L1 as well as targeted L2. This phenomenon is referred to as the system of errors.
Most of adult speakers of different L1 learning Croatian as L2 often have major problems pronuncing palatal
lateral approximant /ʎ/ substituting it with several sounds. The palatal lateral approximant /ʎ/ was corrected in
eight native speaker of South American varieties of Spanish. The tested subjects were recorded before and
after ten sessions of speech correction. Acoustic analysis in Praat showed statistically significant higher F2 in
/ʎ/ in second recording and as well as significant difference in duration. Application of this sort of work can
be seen in foreign language acquisition but also in research of speech-hearing pathology.
Keywords : Verbotonal theory, speech correction, system of errors, palatal lateral approximant / According to the Verbotonal theory, speakers of L1 choose the closest sound from their own
phonological system instead of the correct sound when learning L2 in adult age and the errors are consistent
regarding their common L1 as well as targeted L2. This phenomenon is referred to as the system of errors.
Most of adult speakers of different L1 learning Croatian as L2 often have major problems pronuncing palatal
lateral approximant /ʎ/ substituting it with several sounds. The palatal lateral approximant /ʎ/ was corrected in
eight native speaker of South American varieties of Spanish. The tested subjects were recorded before and
after ten sessions of speech correction. Acoustic analysis in Praat showed statistically significant higher F2 in
/ʎ/ in second recording and as well as significant difference in duration. Application of this sort of work can
be seen in foreign language acquisition but also in research of speech-hearing pathology.
Keywords : Verbotonal theory, speech correction, system of errors, palatal lateral approximant /ʎ/,
acoustic analysis

acoustic analysis